Dynamics of fluid in oscillatory flow: The (Formula presented.) component - Lee, Vincent; Abakr, Y.; Woo, K. (2015)
© School of Engineering, Taylor’s University. In an oscillatory flow, the resistance to flow, more appropriately defined as the impedance to flow, is a function of oscillating frequency, which refers to the harmonic composition of the driving pressure wave. Flow in an elastic tube may be resisted in numerous ways such as the fluid viscosity, fluid inertia and tube elasticity. The concept of impedance arises in the dynamics of the Resistance- Inductance-Capacitance. In oscillating flow, these represent the fluid viscosity, inertia and tube elasticity. This paper describes the effects of impedance, or the Z component as described in-text of an oscillating flow in a valveless impedance pump using numerical simulation. A one-dimensional lumpedsystem model is chosen to perform the analysis in this study. The simulation domain is a mimic to known experimental model previously conducted by Lee et.al. [18-21]. Impedance-induced flow has shown to be combined effects of fluid viscosity, inertia and tube elasticity. Results presented are in reasonable agreement with experimental results presented in Ref [21] with an estimate of 16% variance. This simple model has shown to predict results with significant values, using simple approximations; and further the understanding of fluid impedance’s role in a valveless impedance pump.